Ethical values to enhance higher education for computing - Hameed, Shihab A. (Publications International Lahore, Pakistan, 2014)
The evolution and development for every mankind and society is essentially built on education as a main pillar. The current weaknesses and slow development in the developing countries require an efficient and effective higher education system, especially in computing as an essential path toward bridging the gap with developed countries. Computing education has great role in all aspects of human life (politics, economy, health, and education). Moral and ethical values should introduced to and affect all education process’s elements, which lead to better estimate the shape of the next generation of leaders. The increasing problems in societies force many universities to enhance their education process with ethical and moral values. Historically Islamic based ethical and moral values are consider as a great values and principles for human life that leads to build a stable, effective and healthy society that avoid many social diseases. This paper is to prepare a suitable plan to enhance computing higher education with ethical and values that leads to better evolution of society.